MENINGKATKAN MINAT BELAJAR SISWA PADA PELAJARAN SEJARAH MELALUI PEMBELAJARAN TWO STAY TWO STRAY DI KELAS XI SMA NEGERI 1 SURABAYA - Aria Raharja Hidayat; Corry Liana; Nining Sedyasih (Institute Agama Islam Al-Qolam Malang, 2023)
The purpose of this study was to determine the increase in student learning interest through the Two Stay Two Stray learning model in Class XI SMA Negeri 1 Sidoarjo. This research uses a type of classroom action research with a quantitative approach with descriptive statistical analysis techniques. The data taken consists of data primary and secondary data. The results of the research show that the Two Stay Two Stray model can increase interest in learning history in History Class XI - 5 SMA Negeri 1 Sidoarjo can be said to be running successfully. This is evidenced from the results of the descriptive statistical analysis showing that the average value (mean) is 63.4285 and then the tendency of learning interest is only 5 students to enter into a low response. Not only on that. Student responses get significant changes when the second cycle is implemented. Starting at 65% in the first cycle then becoming 84% in the second cycle.